2012
DOI: 10.1002/eji.201142313
|View full text |Cite
|
Sign up to set email alerts
|

Clonal B cells of HCV‐associated mixed cryoglobulinemia patients contain exhausted marginal zone‐like and CD21low cells overexpressing Stra13

Abstract: A clonal population of B cells expressing a V H 1-69-encoded idiotype accumulates in hepatitis C virus (HCV) associated mixed cryoglobulinemia (MC). These cells are phenotypically heterogeneous, resembling either typical marginal zone (MZ) B cells (IgM +IgD IntroductionHepatitis C virus (HCV) is associated with a spectrum of extrahepatic manifestations, the best characterized of which is type II mixed cryoglobulinemia (MC) [1]. MC is a benign monoCorrespondence: Dr. Massimo Fiorilli e-mail: massimo.fiorilli@un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 49 publications
1
51
1
Order By: Relevance
“…It has been shown that circulating immune complexes are able to activate rheumatoid factor-producing murine B cells, especially in the presence of surrogate T cell help or when they contain nucleosome antigens [18]. We found that V H 1-69 + B cells do not proliferate in response to CpG alone or to the crosslinking of the B-cell receptor with anti-Ig alone, but costimulation with anti-Ig and CpG can elicit a proliferative response, although of low-level [19]. Thus, immune complexes containing DNA or RNA [20,21], such as those formed with microbial components or with nucleosomes, might provide a dual BCR/TLR stimulus capable to sustain low-level self-renewal of anergic MZ-like V H 1-69 + B cells.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…It has been shown that circulating immune complexes are able to activate rheumatoid factor-producing murine B cells, especially in the presence of surrogate T cell help or when they contain nucleosome antigens [18]. We found that V H 1-69 + B cells do not proliferate in response to CpG alone or to the crosslinking of the B-cell receptor with anti-Ig alone, but costimulation with anti-Ig and CpG can elicit a proliferative response, although of low-level [19]. Thus, immune complexes containing DNA or RNA [20,21], such as those formed with microbial components or with nucleosomes, might provide a dual BCR/TLR stimulus capable to sustain low-level self-renewal of anergic MZ-like V H 1-69 + B cells.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, lack of expression of these inhibitory receptors by anergic V H 1-69 + CD21 high MZ-like B cells is intriguing. However, we recently observed [19] that MZ-like V H 1-69 + B cells display constitutive over-expression of phosphorylated ERK and attenuated BCR signaling, a molecular signature of the anergy induced by continual BCR occupancy by antigen [25], and over-expression of the antiproliferative transcription factor Stra13.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed involvement of T-bet + B cells in the response to HIV infection, as T-bet was rapidly induced in B cells during the acute phase and T-bet We and others have previously demonstrated an expansion of CD21 -B cell subsets induced by Th1-type human infections, including HIV, malaria, and hepatitis C (30,31,34,35,(60)(61)(62)(63), and expansion of a clonal CD21 -subset has been described during hepatitis B-and hepatitis C-associated mixed cryoglobulinemia (64)(65)(66). Interestingly, maintenance of expanded CD21 -cells in each of these infections appears to be dependent upon pathogen load (34,35,60,(67)(68)(69).…”
Section: Discussionmentioning
confidence: 98%
“…This is further supported by the specificity of the B-cell receptor of HCV-associated lymphomas for viral antigens, in particular the HCV protein E2 [6,7]. Accordingly, many monoclonal B cells in MC type II and HCV-associated B-cell lymphomas use the immunoglobulin variable (IgV) gene segment VH1-69, which is known to be used both by rheumatoid factors and by some E2-specific antibodies, further supporting a role of antigenic drive in HCV-associated B-cell expansion [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 98%
“…HCV-associated B-cell lymphomas use the immunoglobulin variable (IgV) gene segment VH1-69, which is known to be used both by rheumatoid factors and by some E2-specific antibodies, further supporting a role of antigenic drive in HCV-associated B-cell expansion [8][9][10][11][12]. A second pathogenetic mechanism of HCV on B cells may be a direct mutagenic effect of the virus, including induction of reactive oxygen species [13,14], and of activation-induced cytidine deaminase [15], which is the master regulator for somatic hypermutation of IgV genes and some other off-target genes [16].…”
mentioning
confidence: 99%